Putting China on the couch: Reflections on the development of psychohistory in China - Meng, Fei; Wang, Bo; Chen, Jian (Frontiers in Psychology, 2022)
In the process of reconstructing the history of Chinese psychology, psychohistory once drew little attention. Although applying psychological tools to historical studies has not been a new research method for Chinese historians, when it comes to psychohistory in its modern sense, it inevitably sounds exotic and novel to Chinese academia. However, the significance of psychohistory, especially the one with practical relevance, should not be underestimated. Thus, the history and the deficiency of psychohistory need to be clarified. Based on the macro-historical logic, the development of psychohistory in China can be recounted and divided into four stages, namely (1) before 1902, the pre-scientific stage of psychohistory, (2) 1902–1949, the introduction of modern psychohistory, (3) 1949–1978, the tortuous and lopsided development of psychohistory, and (4) 1978–present, the revival of diverse approaches in psychohistory. The possibilities of psychohistory as we find in such a process, in all its reality, reside in the fact that it could combine the history of ideas with reality and the history of society with ideas, which would undoubtedly improve our understanding of the intertwinement of the human psyche and the social mechanisms, in brief, the historical dynamics. In addition, psychohistory could also help solve psychological problems that the populations in modern times are currently facing. Despite all of these virtues, in terms of indigenization (particularization), generalization (universalization), trans-regional communication, and disciplinary institutionalization, there is still some way for psychohistory in China to go.